(untitled) (Journal of Plant Disease Sciences, 2025)
The present investigation was conducted to detect seed-borne mycoflora of blackgram. Seed samples of ten varieties, namely AKU-15, PDKV Blackgold, Phule Vasu, Phule Rajan, AKU-13-3, TAU-1-42, AKU-16-08, TAU-1, BDU-1 and TAU-62, were collected and examined for seed mycoflora using different detection methods, viz., standard blotter paper method, standard agar plate method and 2,4-D blotter paper method.A total of six seed-borne mycoflora were detected across all the detection methods. The maximum frequency of occurrence was recorded with Aspergillus flavus (20.75%), followed by Aspergillus niger (16.75%) and Fusarium oxysporum (12.83%), whereas the minimum frequency was observed with Curvularia lunata (5.16%), followed by Alternaria alternata (6.38%) and Rhizopus stolonifer (7.88%) in the standard agar plate method compared to other detection methods.Among the varieties tested, TAU-62 showed the maximum association of seed mycoflora by the standard blotter paper method and the 2,4-D blotter paper method. Similarly, the TAU-1 variety exhibited the highest frequency of occurrence of seed mycoflora by the agar plate method. Among the three detection methods, the highest frequency of occurrence was recorded with the agar plate method (69.74%), followed by the standard blotter paper method (50.87%), while the minimum frequency was recorded with the 2,4-D blotter paper method (37.00%). Thus, the agar plate method proved to be the most effective for detecting seed-borne mycoflora of blackgram.